PENERAPAN ASUHAN KEPERAWATAN DALAM PEMENUHAN KEBUTUHAN OKSIGENASI PADA PASIEN DENGAN TUBERKULOSIS PARU DI RSUD ENDE: - M. Fadli, Ferawati; Paschalia, Yustina; Doondori, Anatolia (Kelimutu Nursing Journal, 2024)
Tuberculosis is a disease caused by the mycobacterium tuberculosis bacterium. According to several studies, the increase in the incidence of pulmonary TB is due to lack of early detection, interruption of medication, lack of patient compliance with treatment, and the emergence of resistance (Nisa, 2017). This study aims to describe the application of nursing care in meeting oxygenation needs in patients with a medical diagnosis of pulmonary TB at Ende Regional Hospital. The method used is a descriptive case study design with a nursing care approach. The subject of this research was a patient with a medical diagnosis of pulmonary tuberculosis who was treated at RPD III Ende Regional Hospital. The results of the case study found 2 (two) nursing problems related to interference with meeting oxygenation needs, namely ineffective airway clearance related to retained secretions, and ineffective breathing patterns related to difficulty breathing. Nursing interventions and implementation are designed and implemented with dependent actions such as observation, education and interdependent actions such as collaborative actions. After implementation for 3 days, the nursing problem was partially resolved. It is recommended that patients and families always promote a healthy and regular lifestyle and comply with all recommendations given by health workers to prevent complications